Redesigning innovative healthcare operation and the role of knowledge management - Saito, Murako; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
"This book offers a compilation of chapters on how knowledge impacts the layout and design of the medical industry"--Provided by publisher.
14. Causal relationship among perceived organizational environment, leadership, and organizational learning in industrial workers / Murako Saito -- 15. Eye-movement and performance during reading by cerebral palsy patients / Mitsuhiko Karashima -- 16. Roles of home care and rehabilitation equipment for the aged who need care in improving performance / Hiromi Nishiguchi -- 17. The first attempt of intensive approaches in cognitive rehabilitation in clients with severe traumatic brain injury / Masako Fujii -- 18. Further directions in cognitive rehabilitation in community- and home-based daily trainings in clients with severe traumatic brain injury / Masako Fujii.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 14, 2010).
Keywords: Health services administration; Knowledge management; Health care reform; Medical informatics; Health Services Administration; Health Care Reform; Cognitive rehabilitation; Eye-movement of cerebral palsy patients; Healthcare value; Home care and rehabilitation equipment; Improving organizational performances; Information interpretation in knowledge management; Information processing in knowledge management; Intelligence continuum and emergency and disaster scenarios; Knowledge management in healthcare operations; Organizational learning and leadership; Perceived organizational environment; Electronic books